2017
DOI: 10.15252/msb.20177819
|View full text |Cite
|
Sign up to set email alerts
|

Lysine acetylome profiling uncovers novel histone deacetylase substrate proteins in Arabidopsis

Abstract: Histone deacetylases have central functions in regulating stress defenses and development in plants. However, the knowledge about the deacetylase functions is largely limited to histones, although these enzymes were found in diverse subcellular compartments. In this study, we determined the proteome‐wide signatures of the RPD3/HDA1 class of histone deacetylases in Arabidopsis. Relative quantification of the changes in the lysine acetylation levels was determined on a proteome‐wide scale after treatment of Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
148
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(162 citation statements)
references
References 76 publications
11
148
1
Order By: Relevance
“…Twenty of the 134 proteins modified by both phosphorylation and acetylation (15%) are related to light harvesting and photosynthesis (Figure ). GO enrichment of biological processes involved in light harvesting and photosynthesis (Data S9) further supports the known role of protein phosphorylation and acetylation in the regulation of photosynthesis (Reiland et al ., ; Finkemeier et al ., ; Hartl et al ., ). Previous studies have reported that light‐harvesting and photosynthesis proteins are regulated by either phosphorylation (Longoni et al ., ; Baginsky, ; Allen, ) or acetylation (Hartl et al ., ; Koskela et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Twenty of the 134 proteins modified by both phosphorylation and acetylation (15%) are related to light harvesting and photosynthesis (Figure ). GO enrichment of biological processes involved in light harvesting and photosynthesis (Data S9) further supports the known role of protein phosphorylation and acetylation in the regulation of photosynthesis (Reiland et al ., ; Finkemeier et al ., ; Hartl et al ., ). Previous studies have reported that light‐harvesting and photosynthesis proteins are regulated by either phosphorylation (Longoni et al ., ; Baginsky, ; Allen, ) or acetylation (Hartl et al ., ; Koskela et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Data S11–S16 reveal AcK motifs with both conserved and unique chemical properties and to have significant changes between organs and seedlings, ED and EN, and between subcellular locations. Consistent with motif analyses in both photosynthetic (Konig et al ., ; Smith‐Hammond et al ., ,b; Xiong et al ., ; Zhang et al ., ; Zhen et al ., ; Hartl et al ., ) and non‐photosynthetic (Weinert et al ., ; Henriksen et al ., ; Lundby et al ., ) eukaryotic systems, +1 or −2 phenylalanine/tyrosine‐containing acetylated motifs are found in proteins from all organs and seedlings, whereas the motif with aspartate in the −2 position is unique to seedlings (Figure S5). Diurnal changes in organ and seedling‐specific AcK motifs with a −1 glutamine and a +1 tyrosine were found (Data S11 and S12), in addition to 3× ED‐ and 3× EN‐specific AcK motifs (Data S13 and S14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another well characterized plant PTM is lysine acetylation, which, in addition to other lysine modifications, is available for Arabidopsis and other species in the Protein Lysine Modification (PLM) database (Xu et al ., ). Several studies have highlighted the functional importance of lysine acetylation not only in Arabidopsis (Finkemeier et al ., ; Wu et al ., ; Hartl et al ., ) but also, for example, in rice ( Oryza sativa ) seed development (Wang et al ., ). Although lysine acetylation is reversible, acetylation of the α‐amino group at the protein N‐termini is not and happens either cotranslationally or post‐translationally after protein cleavage events (Bienvenut et al ., ; Drazic et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…N). Protein acetylation motifs vary depending on species, developmental stage and subcellular localization (Hartl et al ). Surprisingly, although most of these motifs have previously been reported in different species, we identified 12 motifs containing two lysine residues in which either lysine could be modified.…”
Section: Resultsmentioning
confidence: 99%